An examination of hypervigilance for external threat in individuals with generalized anxiety disorder and individuals with persecutory delusions using visual scan paths. - Freeman, D; Garety, P; Phillips, M (2000)
One account of generalized anxiety disorder (GAD) is that it results from hypervigilance, manifest as excessive scanning of the external environment and preferential attention to threat. However, for individuals with GAD, there has been no direct study of scanning, and evidence for preferential attention to threat has only been found for threat-words. We therefore devised a new measure of hypervigilance. Visual scan paths were recorded of individuals with GAD (N = 12) and people without a psychiatric illness (N = 12) viewing complex pictures that varied in threat content. People with persecutory beliefs (N = 11) also participated in the study to test the hypothesis that anxiety, via such hypervigilant cognitive processes, may contribute to the maintenance of delusions. Compared with the control group, the anxious individuals were not found either to scan excessively for or to look at threat. The anxiety group was therefore not hypervigilant for external threat, which is inconsistent with the hypervigilance model. As a consequence, the hypothesis that anxiety maintains delusions was not tested. However, additional support was found for the hypothesis that people with delusions form rapid judgements on the basis of less data-gathering than control groups who are either anxious or have no psychiatric illness.